2019
DOI: 10.1111/mmi.14394
|View full text |Cite
|
Sign up to set email alerts
|

Elements in the λ immunity region regulate phage development: beyond the ‘Genetic Switch’

Abstract: Summary Genetic elements in the bacteriophage λ immunity region contribute to stable maintenance and synchronous induction of the integrated Escherichia coli prophage. There is a bistable switch between lysogenic and lytic growth that is orchestrated by the CI and Cro repressors acting on the lytic (PL and PR) and lysogenic (PRM) promoters, referred to as the Genetic Switch. Other less well‐characterized elements in the phage immunity region include the PLIT promoter and the immunity terminator, TIMM. The PLIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…However, this postulated membrane association is not the tight membrane tethering of the λ genome observed by Hallick and Echols (1973). Our two-hybrid data also show the interaction between RexB and RexA (Thomason et al, 2019). Bottom Panel: It is possible that CI, RexB, and RexA colocalize at the periphery of the inner membrane to form a complex that includes all three proteins.…”
Section: Lysogenic State Lytic Statementioning
confidence: 67%
See 4 more Smart Citations
“…However, this postulated membrane association is not the tight membrane tethering of the λ genome observed by Hallick and Echols (1973). Our two-hybrid data also show the interaction between RexB and RexA (Thomason et al, 2019). Bottom Panel: It is possible that CI, RexB, and RexA colocalize at the periphery of the inner membrane to form a complex that includes all three proteins.…”
Section: Lysogenic State Lytic Statementioning
confidence: 67%
“…Thus, the CI-RexB interaction likely occurs via the RexB central cytoplasmic loop (Figure 13). We previously showed that RexA and RexB physically interact in vivo (Thomason et al, 2019). The strength of the RexA-RexB interaction (108 β-galactosidase units), however, is slightly lower than that of RexA with CI ( the molecular level, we suspect that the Rex system functions as a rheostat that modulates phage repressor protein interactions to fine-tune the bistable switch, with RexA and RexB each having independent and complementary effects as the phage switches from lysogenic development to lytic growth (see Figure 12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations